The Ability of The Second Years Students of SMAN 2 Sungai Penuh in Using Question Tags - Yelnim Yelnim; Sukarta Kartawijaya; Intan Sherlin (Syntax Corporation Indonesia, 2021)
This reseach is aimed at analyzing the ability of the scond years student’s of SMAN 2 Sungai Penuh in using qestion tag. This research was done at SMAN 2 Sungai Penuh. The prposes of the reseach are (1) To know the student’s ability ini using tag in English sentences. (2) To Know, what the student’s weakness using question tag in English sentences.(3)To now, wha the efort taken by teacher to improve student’s ability using question tag in English Sentences. The analysis focuses on learning about question tag. The data are collected by using obsevational method in collecting data, gives test some student’s with 20 item test. The informan of the reseacrh is 10 student’s each of class as sample. The analysis is coducted by using descripive quantiative method which is meant to envelope fact, situation, variable and phenomenon that happen a te time when the reseach takes places and present in with reality. The result shows that the student wakness in using question tag in english sentences. (1) the ability of student in using question tag in sentences low category with score 57% (2) the stdents did not know concept in each of sentences. (3) the student could not difference word that added s or es.